Saliva Secretion and Efficacy of Helicobacter Pylori Eradication in Peptic Ulcer Patients - M. Vahedi; AR. Khalilian; Sh. Abdollahzadeh; N. Shafiei (Tehran University of Medical Sciences, 2011)
Objective: It has been noted that the presence of Helicobacter pylori (H. pylori) in the oral cavity may affect the outcome of eradication therapy. This condition is associated with the recurrence of gastric infection. The optimum secretion of saliva promotes oral health consequently influencing H. pylori eradication. The purpose of this study was to investigate the relation between salivary secretion and the efficacy of H. pylori eradication from the stomach. Materials and Methods: Forty five patients with gastric H. pylori infection were enrolled in this study. Diagnosis of H. pylori infection was confirmed by endoscopy, biopsy, urease test and histological examination. Salivary secretion of all participants was determined under standard condition before the beginning of antibacterial treatment. Then the patients were treated with a 14-day course anti-H. pylori regimen consisting of amoxicillin, omeprazole, metronidazole and bismuth. The efficacy of eradication therapy was evaluated 4 weeks after the end of the treatment course. Mann-Whitney U test was used to analyze the variables. Results: The median of salivary secretion among successful and unsuccessful H. pylori eradication groups was 0.48 ml/min and 0.24 ml/min, respectively (p=0.005). Conclusion: Although the type of drug regimens is challenging, the efficacy of H. pylori eradication from the stomach might be reduced by lower salivary secretion.